Impact of Postprandial Lipemia and Glycemia on Inflammatory Factors in over 1000 Individuals in the US and UK: Insights from the PREDICT 1 and InterCardio Studies. (29th May 2020) - Berry, Sarah; Mazidi, Mohsen; Franks, Paul; Valdes, Ana; Sattar, Naveed; Wolf, Jonathan; Hadjigeorgiou, George; Drew, David; Chan, Andrew; Segata, Nicola; Asnicar, Francesco; Spector, Tim; et al.
Abstract: Objectives: Postprandial glycemia (PPG) and lipemia (PPL) initiate an acute inflammatory response, which may be relevant to future CVD. We characterised the impact of PPL and PPG on inflammatory responses using traditional (IL-6) and emerging (glycoprotein acetyls; GlycA) biomarkers of inflammation in a large scale, tightly controlled study (PREDICT 1; NCT03479866) and an independent validation study (InterCardio; NCT03438084). Methods: The PREDICT 1 dietary intervention study of 1102 healthy individuals from the US and UK, assessed the postprandial (0–6 h) metabolic responses to sequential mixed-nutrient meals (50 g fat and 85 g carb at 0 h; 22 g fat and 71 g carb at 4 h). Baseline microbial diversity (16S Shannon diversity) and visceral fat mass (VFM; based on DXA) were also measured. Results were validated in an independent randomised crossover trial ( n  = 50). For both studies, glucose, triacylglycerol (TG), IL-6 and GlycA were measured at multiple intervals. Results: In PREDICT 1, GlycA and IL-6 concentrations increased significantly after meals (by 4.5 and 169%; peak 6 h, respectively) but were not correlated. Peak postprandial TG and glucose concentrations were strongly associated with GlycA ( r  = 0.832 and r  = 0.239, respectively) but not IL-6. Machine learning with cross-validation, revealed that PPL was the strongest predictor of postprandial GlycA. There was evidence of an interaction; individuals with higher microbial diversity and lower VFM had an attenuated inflammatory response. Individuals eliciting an enhanced response (30% rise at 6 h) had higher predicted CVD risk compared to the rest of the cohort. In the InterCardio study, the postprandial inflammatory increase in GlycA was also significantly correlated with PPL and varied within the four different types of fat tested. Conclusions: In the first study to investigate postprandial inflammation at scale, we observed that PPL was a stronger determinant of systemic inflammation compared with PPG. The clinically significant and variable postprandial inflammatory response, and its association with lipemia and glycemia, highlights the potential for personalized dietary strategies to lower postprandial metabolic responses to reduce low grade inflammatory related diseases. Funding Sources: NIHR, Wellcome Trust, Zoe Global Ltd, BBSRC DRINC.